2015
DOI: 10.1007/s00167-015-3608-6
|View full text |Cite
|
Sign up to set email alerts
|

Do graft diameter or patient age influence the results of ACL reconstruction?

Abstract: Retrospective case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 39 publications
(74 reference statements)
1
24
0
1
Order By: Relevance
“… 22 , 23 Several studies have also reported a higher graft failure rate in young and more active patients. 7 , 24 , 25 However, only graft size was shown to be an independent predictor of graft failure in our logistic regression analysis. We noted in our series that 76% of female patients and 36% of male patients had graft at risk for failure based on size (<8 mm in diameter).…”
Section: Discussionmentioning
confidence: 60%
“… 22 , 23 Several studies have also reported a higher graft failure rate in young and more active patients. 7 , 24 , 25 However, only graft size was shown to be an independent predictor of graft failure in our logistic regression analysis. We noted in our series that 76% of female patients and 36% of male patients had graft at risk for failure based on size (<8 mm in diameter).…”
Section: Discussionmentioning
confidence: 60%
“…The same year, Marchand et al 23 reported on the laximetric outcomes (using GNRB® [Genourob, Laval, France] as a measurement tool) of 88 hamstring ACL reconstruction patients operated using a four-strand isolated ST or a doubled ST-G 4-strand graft with an average follow-up of 26 months. The diameter of the central portion of the graft prepared was measured using a calibrator.…”
Section: The Relationship Of Graft Size With Acl Reconstruction Failumentioning
confidence: 99%
“…There are obviously other factors that should be considered, especially age 18 , 19 , 23 (probably the most important risk factor for revision). Therefore, a larger graft size should not be taken as the unique single goal in ACL reconstruction.…”
Section: Summary and Recommendations From The Evidencementioning
confidence: 99%
“…8 A biomechanical study that tested 6 to 9 mm hamstring allograft suggests that increasing tendon diameters by 1 to 2 mm will significantly lead to better graft strength. 4 A study demonstrated that four-strand hamstring graft is stiffer and stronger than the original ACL or 10 mm patellar ligament graft, 13 while other study compared postoperative laximetric measurement between 8 to 10 mm hamstring graft suggested that no benefit to increase the diameter of graft above 10 mm 17 Spragg et al 18 stated that every increasing by 0.5mm increase in graft diameter lead to 0.82 times lower revision surgery. Another study recommended that minimum diameter of the graft was 7mm.…”
Section: Discussionmentioning
confidence: 99%